Enhancing the quality of education in Nigeria through a human rights-based approach (2015)
This article articulated an overview of the concept of human rights and its linkages to education. It examine the definition, attributes and classifications of human rights, arguing that, a human right based approach to education is imperative for Nigeria in keeping up with global minimum standards and currency in a globalised world. It outlines the framework of laws on education at the international, regional (African) and national (Nigerian) levels. It notes that the right to education in Nigeria is in Chapter II of the Constitution of the Federal Republic of Nigeria (CFRN) 1999 titled: Fundamental Objectives and Directive Principles of State Policy in sections 16 and 17, meaning that the obligation of the government is at the level of objective policy of the state which may not ordinarily be enforced in the same way as the rights in sections 33-46 of the CFRN 1999, for which individuals may sue the government for violation. Since human rights laws define government obligations and mandates in educational provisions and influence national education strategies, the article examine the necessary elements and advantages of a right-based approach to education. It concluded by recommending that it is necessary for Nigeria to integrate and fully implement the rights based education approach at all levels of education in the country to make education holistic